KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MOTIVASI KERJA GURU SEKOLAH DASAR DI KECAMATAN NGAMPRAH - Kurniawati, Nita; Zuhaery, Muhammad; Hidayati, Dian (STKIP Pesisir Selatan, 2025)
Teacher work motivation is a major factor in the success of the learning process. Therefore, the success of an education will not be separated from the role of the principal's leadership, the principal's leadership is very important because the principal has a role in developing and achieving school goals. This study aims to determine the Leadership of Elementary School Principals in Ngamprah District, West Bandung Regency. This study uses a qualitative descriptive approach, namely careful carving of certain social phenomena. The results of interviews in the field with the Principal and teachers in improving teacher Work Motivation. The first is the Principal's Leadership by looking at how the leadership and communication styles in the school, the principal's support, Appreciation and work environment. In order to improve teacher work motivation, effective communication steps are taken, opening communication between teachers, innovation in facilities and infrastructure that can support students and teachers in carrying out teaching and learning activities and creating a comfortable work environment. The influence of Principal Leadership in improving teacher work motivation can be established well because of Cooperation, a sense of belonging, togetherness between the principal, teachers, students and parents and the desire to be able to continue to progress and grow together.